GLOBAL PASSWORD FOR EASE OF USE, CONTROL AND SECURITY - Untung Rahardja; Valent Setiatmi; Dhita Rukmianti (Universitas Raharja, 2010)
Authentication is applied in information systems for maintaining the confidentiality and data security. Commonly used way is by giving a password. However, the authentication process as it may cause inconvenience for both users and administrators, ie if they are in environments that have many dijferent systems, where in each cf these systems implement an authentication process dijferent from one another. Through a global method of password, a user does not need to enter passwords repeatedly to enter into multiple systems at once. In addition, administrators also do not need to adjust the data in each database system in case a user changes to data. In this article, identified problems faced by the company in terms of authentication using passwords on web-based information systems, defined seven characteristics of the concept of a global method of authentication with a password as a troubleshooting step, and determined the benefits of mplementing these new concepts. In addition, the displayed listing program written using ASP script and its implementation on the Student Information Services (SIS) Online JRS in Higher Education Prog. In the global method of passwords, not only the security level is concerned, but also convenience and ease both in the process of using both at the time control.